The Asian modern : culture, capitalist development, Singapore - Wee, C. J. Wan-ling (Hong Kong University Press, 2007)
Wee's narrative refuses to accept the uncritical interpretation of the modernizing processes in Asia as liberation from the hegemony of Euro-American capitalism. Nor is Wee prepared to concede that all cultural initiatives in the postcolonial societies are, therefore, denied all power to devise alternative forms of expression in the face of this haunting presence.